Capitalism in American Society as Represented in Upton Sinclair’s The Jungle - Bakthawar, Puri (LANTERN (Journal on English Language, Culture and Literature), 2013)
Nowadays, there is a phenomena about capitalism which becomes the main system in the world. Although capitalism becomes the main system in the world, there are some criticisms to capitalism. In one viewpoint, capitalism gives much wealth to capitalist class. On the other hand, capitalism becomes the main problem that gives miserable life to working class who is oftenly exploited by capitalist class in order to get profit, as represented in Upton Sinclair's The Jungle. In this thesis, the writer is interested to analyse how capitalism influences the miserable life of working class. The writer analyses a novel entitled The Jungle by Upton Sinclair as the object of research. The focus of this thesis is how capitalism becomes the main factor which causes the miserable life of working class. The main purpose of this thesis writing is to show the criticism to capitalism that gives miserable life to working class as represented in Upton Sinclair's The Jungle. In analysing the data, the writer uses library research method. In analysing intrinsic aspects of the novel, the writer uses some theories about theme, setting, character, and plot. While in analysing the extrinsic aspects of the novel, the writer uses some theories about capitalism, Marxist Literary Criticism, and alienation. The result of the research shows that there are a lot of criticisms to capitalism because capitalism becomes the main factor that gives miserable life to working class. In The Jungle, capitalism gives influence to social aspects of human life that lead the miserable life of Jugis and his family as the representation of working class. Capitalists class also exploits and treats working class badly. Moreover, there is a phenomena about alienation which estranges Jurgis and his family from humanitarian values as the effect of capitalism. Based on the result of the research, it can be concluded that capitalism fails in giving prosperity to working class, even capitalism becomes the main factor that gives miserable life to working class.